Mengembangkan Kemampuan Matematika Melalui Metode Bermain Kartu Angka Bergambar Pada Anak Kelompok B TK Aisyiyah Kratonan Tahun Ajaran 2014/2015 - Yuliana, Eni (2016)
The objective of this research was to develop the mathematical ability in the children of group B of TK Aisyiyah Kratonan in the academic year of 2014/2015 through pictorial number card. Kind of this research was a Classroom Action Research. Subjects of this research were the children of Group B of TK Aisyiyah, Kratonan urban village, Serengan sub district, Surakarta municipality, with the amount of 20 children. The data needed in this research were the mathematical ability and the learning used the method of playing the pictorial number card. The technique of data collection was observation. The instrument used was the guidance of observation. The techniques of data analysis were the technique of comparative analysis and the technique of interactive analysis. Based on the results of the research, it could be concluded that the method of playing the pictorial number card could develop the mathematical ability of the children of group B in TK Aisyiyah Kratonan in the Academic Year of 2014/2015. It could be seen from the percentage average of every cicle in which in the pre-cycle was 35% that meant that the children had not been developed, the cycle I was 58.47% that meant that the children began to develop, and the cycle II was 90.42% that meant that the children developed very well.